(untitled) (Colloquia Comparativa Litterarum, 2025)
My goal is to present the reception of several writings by Emil Staiger in the Bulgarian academic environment. Also – to pose a more general question – do approaches to these writings imply credibility? The publications I discuss are by Rossitza Dimtshewa, Nikola Georgiew, Atanas Natew.